Self-assembled Metal Organic Framework Microflowers as Polysulfides Immobilizers for Lithium Sulfur Batteries - Dou, Xiaoyuan (University of Waterloo, 2019)
A unique flower-like metal organic framework (ZnHMT) is synthesized by a facile and efficient method. The obtained ZnHMT microflowers were employed for the construction of a multifunctional interlayer towards improved Li-S batteries. Through synthetic optimization, uniform ZnHMT microflowers can be obtained through the fast self-assembly of ultrathin 2D nanosheets within a few minutes under ambient temperature. When implemented as interlayer in Li-S configuration, the as-developed ZnHMT microflowers demonstrate a strong affinity with polysulfides through Lewis acid-base interaction, which effectively confines sulfur species within the cathode section, leading to a significant inhibition on polysulfide shuttling. Moreover, the flower-like assembly architecture not only exposes sufficient absorption sites for sulfur immobilization, but also afford a facile electrolyte infiltration and ion transfer, thus contributing to a fast and durable sulfur electrochemistry. Consequently, Li-S batteries based on the ZnHMT functional separators and simple carbon-based cathodes achieved an excellent cycling stability with a low capacity decay rate for 800 cycles under 1C, superb rate performance up to 5 C, and high areal capacity at raised sulfur loading of 4.5 mg cm-2. These results confirm the great capability of the as-developed ZnHMT interlayer in boosting the battery performance, which not only offers an easy access to high-performance Li-S batteries but could also enlighten the material designs in other related energy storage and conversion fields.
Keywords: lithium sulfur batteries; polysulfides immobilizers; metal organic frameworks; functional separators